Process Improvement and Employee Velocity in the Nigerian Banking Sector: The Case of Some Selected Banks in South West, Nigeria - Olota, Oluwayomi (Universidad Francisco de Paula Santander, 2025)
In recent years, financial institutions have increasingly recognized the critical role that organizational processes play in driving productivity and employee satisfaction. Hence, this paper examined aims to investigate process improvement’s effect on employee velocity in the Nigerian banking sector; the case of some selected banks in south west, Nigeria. Specifically it examined: the effect of continuous improvement initiatives, process monitoring and benchmarking on employee velocity. Survey research design was adopted with a population of two hundred and twenty-one (221) staff. 142 individuals were determined to be the final sample size using Taro Yamane’s formula for determining sample sizes. Data collected was analyzed using PLS-SEM. Findings revealed that process monitoring has the strongest effect on employee velocity (β = 0.451, t = 6.739, p < 0.000), followed by Benchmarking (β = 0.223, t = 3.882, p < 0.000), and continuous improvement initiatives (β = 0.191, t = 3.045, p = 0.002). It concluded that process improvement is significantly vital for employee velocity of in Nigeria banking sector. It therefore strongly recommended that organizations should prioritize process monitoring, continuous improvement initiatives, and benchmarking in order to increase employee velocity. Establishing a benchmarking team to examine industry norms and spot performance gaps would help achieve this.